A GRID-CONNECTED PV ARRAY AND BATTERY ENERGY STORAGE-BASED EV CHARGING STATION WITH ENHANCED POWER QUALITY USING FOPID CONTROLLER - Mr. C Tharun Kumar,; Mr. M Seenivasan,; Mr. Pandiyan V,; Mr. P R Rajeev, (Utilitas Mathematica, 2024)
This paper presents an advanced grid-connected electric vehicle (EV) charging station integrated with a battery energy storage system (BES) and a photovoltaic (PV) array. To further enhance the system’s performance, a fractional-order proportional-integral-derivative (FOPID) controller is incorporated to minimize grid voltage and grid current total harmonic distortion (THD). The charging station operates efficiently in both standalone and grid-connected modes, ensuring optimal power management. The positive sequence components (PSCs) of the three-phase grid voltages are evaluated for estimating unit templates (UTs) and reference grid currents, which improve synchronization with the point of common coupling (PCC). A bidirectional buck-boost converter is used for interfacing the EV and BES at the DC link. During the daytime, EVs are charged directly from the PV array, while in the absence of solar power, energy is drawn from the grid or BES. The proposed FOPID controller enhances dynamic response, reduces settling time, and improves grid stability by effectively mitigating harmonics. Experimental results on a laboratory prototype validate the effectiveness of the proposed system, demonstrating significant improvements in grid power quality and THD reduction.